Evaluating School Operational Assistance Funds Implementation Policy in East Java Province - Slamet Hari Sutanto; Vindha Tyas Restyaningati; Ervan Kusindarto (STAI Hubbulwathan Duri, 2021)
This study evaluates the implementation of School Operational Assistance Costs for Education (BOS) policy to increase school participation rates in elementary, secondary, and high school levels, both public and private, in East Java. This research is a systematic literature review that gathers existing data. The researchers surfed the largest web search engine for scholarly literature, Google Scholar, to collect the data. Five articles that represented the implementation of BOS Funds in East Jawa were selected as the data. To analyse the data, the researcher used Miles Huberman’s (1994) analysis steps, namely data reduction, data verification, and data display. The conclusion of the research results showed that the Education BOS program's budget allocation had been directed to improve the quality of learning. Almost most aspects of the implementation of Education BOS program have been implemented properly according to the Technical Guidelines BOS. The scope of financing, which is included in the allocation of the use of BOS for Education Administration and School Operational Assistance, is sufficient to support the implementation of the free school policy. However, the unit cost per student indeed needs to be re-evaluated by giving affirmations or special treatment, especially on the aspect of accessibility, for poor private schools and schools with very few students or schools that are geographically remote and isolated in rural areas to be given an additional unit size cost per student.